Shadow of power : a Paul Madriani novel - Martini, Steve, 1946- (William Morrow, 2008)
A hate crime involving the murder of a legal scholar who had made his career by penning controversial works places defense attorney Paul Madriani in a media spotlight that compromises his investigation into an elusive witness within the cloistered confines of the Supreme Court.